Numerical Study of Thermal Hydraulic Performance Improvement in Double Pipe Heat Exchangers Using Different Corrugated Tube Geometries - Muhammad Hisyam Haidar Al Ghazi; Damora Rhakasywi; Fahrudin Fahrudin (Institut Teknologi Adhi Tama Surabaya, Indonesia, 2026)
Enhancing thermal efficiency in double-pipe heat exchangers has become a key industrial priority to reduce energy consumption, with passive methods such as pipe geometry modification receiving significant attention. This study investigates the comprehensive thermal and hydraulic performance of concave corrugated tubes (CCT) with triangular, square, and trapezoidal profiles. A three-dimensional numerical simulation was employed, utilizing the finite volume method and the SST k-ω turbulence model over a Reynolds number range of 7700 to 13,800. The results indicate that all CCT geometries improve thermal performance compared to plain tubes, with the square profile showing the highest increase in Nusselt number (13.87–16.59%). This enhancement is attributed to higher turbulence intensity, which, however, also results in the greatest hydraulic penalty due to dominant form drag. Performance Evaluation Criteria (PEC) analysis yielded values above 1 for all geometries, with the square profile being optimal at lower Reynolds numbers, whereas the triangular profile outperformed the others at higher flow rates (Re 12,300), with a PEC value of 1.023. In conclusion, corrugated geometries have been shown to enhance thermal performance, but the associated hydraulic penalties necessitate careful selection based on the operational flow range to achieve an optimal balance between heat-transfer gains and pumping-power requirements.